Analisis Profit Margin PT Bank Sumut Kantor Pusat Imam Bonjol Medan - Harianja, Riodinar; Sianipar , Selvie; Martaulina , Sinta Diana (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Profit margin analysis of Bank Sumut Head Office, Imam Bonjol Medan refers to the report of the Financial Services Authority of the Republic of Indonesia, is one of the assets of the local government (North Sumatra) in banking services. The activities of this company also have an interest in financial statements in profitability. The increase in profit each year refers to the financial statement process at least the profit earned per year has increased significantly. This study aims to describe the performance of one of the banks owned by the North Sumatra Regional Government in the 2017-2021 period. This period is a phenomenal analysis during the Covid-19 period in the financial sector owned by regional development banks. The method used in this research is descriptive analysis method, which describes the situation of financial statements pre to post Covid-19 passed. The research findings show that profit margin on sales (net profit margin and gross profit margin) experienced fluctuations in percentage of 16% - 24%. The transition period of Covid-19 to the new normal era has a very dominant impact.